Study on Hydraulic Characteristic of Unsteady Flow at Huangchigou Water Distribution Hub by Observing Instantaneous Water Level Based on Single-Camera and Fixed-Scale Compensation Method. (16th February 2023) - Ding, Weihua; Zhu, Lin; Li, Hu; Hou, Bin; Yang, Fan; Wang, Xinhong
Abstract : The Huangchigou Water Distribution Hub is the core water distribution structure in the Hanjiang-to-Weihe Valley Water Diversion Project. It plays a decisive role in ensuring the safety of downstream water transport, allocating water reasonably and reducing the waste of abandoned water. The study on its unsteady-flow hydraulic characteristics is of key significance in the formulation for the opening and closing rules of the hub gates. The shape of the instantaneous water surface profile is an important factor for the hydraulic characteristics of the unsteady flow in the hub. The effect of the traditional instantaneous water level measurement method is not ideal. A single-camera and fixed-scale compensation method is proposed for an instantaneous water level observation. The proposed method meets the requirement of measurement accuracy and reduces the observation cost of the model test. The unsteady-flow test of the hydraulic model in the Southern Main Tunnel of the Huangchigou Water Distribution Hub was carried out under two operating conditions when the model flow is 0.0246 m 3 /s. Precise data such as wave front propagation velocity and hydraulic oscillation recovery time of unsteady flows in the Southern Main Tunnel was obtained. It has an important reference value for the research and design of water transfer dispatching and gate-opening and gate-closing rules for the Huangchigou Water Distribution Hub.